Clinical and laboratory characteristics of paediatric systemic lupus erythematosus at secondary level hospital among local population in North East India - Aier, Tenukala; Joe, Chippy Hanna; Kikon, Sulanthung; Tsanglao , Wonashi (International Journal of Contemporary Pediatrics, 2024)
Background: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease characterized by multisystem inflammation and the presence of circulating auto antibodies directed against self-antigens with flare-ups and remissions. Childhood-onset SLE (cSLE) is a rare disease with an incidence of 0.3-0.9 per 100.000 children-years. The study among paediatric population of north east India were few and hence this study from north east India was undertaken. Objective of this study was to study the clinical and immunological profile of children with systemic lupus erythematosus (SLE). To study the distribution of Renal Lesions according to ISN/RPS Classification of Lupus Nephritis. Methods: Retrospective observational single centre study at secondary care hospital in North East India. Medical records of children with SLE admitted in Paediatric department from the period of 2018-2024 through the hospital information management were analysed. Clinico pathological features and immunological profile were compared with other studies. Results: Among 20 patients studied female to male ratio was 3:1. The mean patient’s age at the time of presentation was 12.4 years. The mean duration of illness was 8.5 months. Most common systems involved were hematological (85%), followed by kidney (75%) and mucocutaneous (75%). All (100%) cases were ANA positive. 45% were anti smith antibody positive, 20% were anti- dsDNA positive. Focal and segmental proliferative glomerulonephritis (ISN/RPS class III) was the most commonly seen histological pattern, seen in 5 (83%) patients who underwent biopsy. Diffuse proliferative glomerulonephritis (ISN/RPS class IV) was seen in 1 (16%) patient. Conclusions: Childhood onset SLE is still a challenge to diagnose and manage due to unpredictable clinical manifestations with variable disease activity at different age.